Strengthening Community Religious Awareness through Mosque Management: The Role of Takmir at Sholeh Umar Syahlan Mushola, Kujon Hamlet - Heksi Megannanda; Hafidz Hafidz (FKIP - Universitas Riau, 2026)
This study analyzes the efforts of the Sholeh Umar Syahlan Mosque administrators to enhance religious awareness among local residents and evaluates the effectiveness of these initiatives within the community’s socio-religious life. A qualitative field research approach with a phenomenological design was employed to explore participants’ lived experiences. Data were collected through observation, in-depth interviews with mosque administrators and residents, and document analysis. Credibility was ensured through methodological and source triangulation, while data were analyzed using Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that religious awareness is fostered through structured yet accessible programs encouraging active participation, such as Qur’anic recitation, TPA, tahsin sessions, and social-religious activities. These initiatives strengthen congregational worship, deepen religious understanding, and reinforce social solidarity. Despite limited financial and human resources, adaptive and participatory management enables the mosque to function effectively as a sustainable center for religious and social development.